Evaluasi dan Analisa Kinerja Proyek terhadap Biaya dan Waktu Penjadwalan Menggunakan Pendekatan Earned Value Method (Studi Kasus Proyek Air Receiver Tank) - Maulina Septa Dwi Anggraini; Renanda Nia Rachmadita; Aulia Nadia Rachmat (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Abstract - Industrial and construction projects are one of the sectors that support economic growth in Indonesia. Projects are required to be managed to achieve the targets that have been set. One of the construction companies PT. LDP specializing in engineering received the Air Receiver Tank project from one of the clients and the project was delayed from a predetermined deadline. Such delays have consequences for the decrease in client confidence in the performance of the company. Therefore, evaluation and analysis related to the performance of the project are required to the time and cost of the project using the Earned Value Method (EVM). Scheduling analysis uses Precedence Diagram Method (PDM) and crashing to speed up the duration of project completion. The results of the study based on EVM analysis showed that the project experienced delays with an estimated project completion time of 88 days and an estimated project completion cost of Rp662,241,998.41. Based on the analysis using PDM and crashing obtained the results of acceleration from 95 days to 65 days. The acceleration alternative used is to increase the workforce by 50% with a cost increase of 13.89% of the direct labor cost at the actual duration